2010
DOI: 10.1136/oem.2010.055939
|View full text |Cite
|
Sign up to set email alerts
|

Individual and organisational determinants of use of ergonomic devices in healthcare

Abstract: ObjectiveThis study aims to identify individual and organisational determinants associated with the use of ergonomic devices during patient handling activities.MethodsThis cross-sectional study was carried out in 19 nursing homes and 19 hospitals. The use of ergonomic devices was assessed through real-time observations in the workplace. Individual barriers to ergonomic device use were identified by structured interviews with nurses and organisational barriers were identified using questionnaires completed by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 33 publications
2
35
0
1
Order By: Relevance
“…Three intervention studies have suggested that limited use of the available lifting equipment is a possible reason for a lack of reduction in musculoskeletal injury claims9 28 or prevalence of LBP 27. Recent studies on primary preventive interventions on manual patient handling in healthcare settings have identified many barriers at an individual and organisational level that hampered appropriate implementation 33 34…”
Section: Discussionmentioning
confidence: 99%
“…Three intervention studies have suggested that limited use of the available lifting equipment is a possible reason for a lack of reduction in musculoskeletal injury claims9 28 or prevalence of LBP 27. Recent studies on primary preventive interventions on manual patient handling in healthcare settings have identified many barriers at an individual and organisational level that hampered appropriate implementation 33 34…”
Section: Discussionmentioning
confidence: 99%
“…For example, when there is a conflicting demand for these devices, male nurses may give priority of use to their female nurse colleagues. The level of lift use measures actual utilization for patient handling when needed; both organizational and individual factors play roles in the level of actual use (Koppelaar et al, 2011;Rickett et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of mechanical lift equipment at reducing the biomechanical load of patient-handling tasks has been supported in a controlled laboratory setting (8); however, studies offer different conclusions of the effectiveness of patient-lifting equipment (often implemented in conjunction with other intervention components) at reducing adverse MS conditions among workers in patient-care settings (15)(16)(17). A number of barriers to the use of lift equipment have been described (18)(19)(20); studies suggest mechanical patient lifts are not regularly used in patient care tasks (1,(21)(22)(23)(24)(25). Although equipment effectiveness has been demonstrated in the long-term care setting (23,(26)(27)(28)(29)(30)(31)(32), results may not be generalizable to the acute care setting, which is characterized by more extensive patient turnover, frequent and abrupt changes to patient acuity, a variety of patient…”
mentioning
confidence: 99%